Pelatihan Penggunaan Sistem Informasi Perpustakaan Berbasis Web Untuk Mendukung Efektivitas Layanan Peminjaman Dan Pengembalian Buku Di SMP Negeri 1 Klambu - Arina Fawaida; Muhammad Arifin (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The training on the use of a web-based library information system at SMP Negeri 1 Klambu is a community service activity aimed at improving the effectiveness of book borrowing and returning services within the school. Previously, the management of book data, members, and transactions was conducted manually, often leading to recording delays, data loss, and reporting difficulties. Through this training, the team introduced a web-based information system designed to help librarians manage data in an integrated, fast, and accurate manner. The method includes initial observation of library conditions, development of a web-based system with core features for book, member, and transaction management, and direct training sessions for library staff and teachers. The results indicated an improvement in the efficiency and orderliness of borrowing and returning services, allowing for faster transactions and better documentation. This program not only enhanced the technological capability of the library staff but also fostered a culture of digital transformation within the school environment. Therefore, the activity provides a valuable contribution to improving educational service quality at SMP Negeri 1 Klambu.